Ophthalmological aspects of the inhabitant of the Andean highlands - Valdeavellano, Jorge (1951)
The existence of populated areas at altitudes of 2,000 to 5,000 meters and its constant residence in them; gave rise, over the centuries, to the formation of acclimatized subjects, provided with special biological features that allowed them to bravely face unfavorable environmental conditions prevailing at that point. Such individuals have come to build a true climato-physiological range of human race.